Phasmarhabditis safricana n. sp. (Nematoda: Rhabditidae), a parasite of the slug Deroceras reticulatum from South Africa - Ross, Jenna L.; Pieterse, Annika; Malan, Antoinette P.; Ivanova, Elena (Zootaxa, 2018)
During a survey for mollusc-associated nematodes in South Africa, a new Phasmarhabditis species was isolated from the invasive slug, Deroceras reticulatum, collected from a nursery near George in the Western Cape province. The nematode was identified using a combination of morphological, morphometric, molecular, and phylogenetic techniques. The new species, P. safricana n. sp., is characterised by the cupola-shaped tail of the female with a spike, small, non-protruding phasmids, a fingerprint-like pattern of the cuticle covering the female tail, toothlike cephalic structures of the infective juveniles, and the distinct molecular characteristics of the species. The molecular phylogeny of the new species, as inferred from its SSU and LSU rRNA gene, places P. safricana n. sp. in close proximity to P. papillosa. Virulence tests were conducted, which demonstrated that P. safricana n. sp. caused significant mortality to the European invasive slug, D. reticulatum. The new species brings the total complement of the genus to eleven species.